Control de la sigatoka negra mycospaherella fijiensis morelet con dos sistemas de atomizaciòn aérea en una finca orgánica - Aguilar Noblecilla, Jean Pierre (2018)
The present work was carried out in the banana farm "Agriofán"; address vía Balosa, Machala-Santa Rosa, km 17.5. There are different companies that provide fumigation services via aerial and terrestrial means of transportation, with calibrated aircrafts and motor pumps respectively. In this project the same fumigation service is compared to a different type of transportation, as it is the helicopter, to determine whether the mean used to fumigate has an impact when controlling the disease. Which occurs in many cases, at the beginning of winter in a very aggressive way, the same that decreases the leaf area of plants and reduces production. The general objective was to deal with the determination of the use of fumigation helicopters to control the black Sigatoka in front of the atomization equipment of the aircraft and the earth (motor pump) in an organic banana plantation, within the specific objectives of the investigation. the number of times per type of application, the severity of the infection between these three systems and the evaluation of the affected leaf area using the methodology of Dr. Stover, for sheet 1 that was marked at the beginning of the investigation. The evaluated data were, number of drops per cm2, in sheets 1, 3 and 5, in addition severity was evaluated at 90 days after the application in sheet 1 mark at the beginning of the trial, on average this sheet remained in position 8th and 9th leaf of the selected plants. The results of the investigation according to the methodology to evaluate the infection of black Sigatoka, in the Agriofan farm. The ANOVA table breaks down the variance by drop size into two components: a component between groups and a component within the groups for which the case is equal to (59.7051) and (107.134), is the estimated value between groups and estimated within of the group since the P-value of the F-test less than 0.05, there is a significant statistical difference between the means and a level of 95.0% confidence. In the same way that the means are different from the others, in the list of tabular options as in figure 1 it is shown that it has a significant difference for the treatment T1, with an average of 45.40 drops / cm2 sheet 1 , with the application of the helicopter for the treatment T2 and T3, the amount of drops in the paper of sheet 3, according to the amount of drops in the treatment, T1 and T3 (48.6) drop / cm2 shows a difference statistics when compared with the treatment T2 (24.2) and T3 (19.8) drop / cm2. when comparing the results of the analysis of sheet 5 the number of drops in the behavior that is equal to the sheets 1 and 3, where the helicopter presents the greatest number of drop numbers / cm2. For the treatment result T2 and T3 there is no difference between the treatments of the work performed.